Impact of fashion entrepreneurship programme on entrepreneurial interests, intention and competencies - Arasinah Kamis (Tanjong Malim, 2019)
Impact of fashion entrepreneurship programme on entrepreneurial interests, intention and competencies by Arasinah Kamis